PERTANGGUNGJAWABAN NOTARIS DALAM PEMBUATAN AKTA PARA PIHAK (PARTIJ ACTE) DAN AKTA PEJABAT (RELAAS ACTE) - Yunus, Andi Yuliana (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Indonesia as rule of law give main guarantee on certainty, order and legal protection. This guarantee can be given by proofs which determine clearly on rights or obligations of legal subject, one of those is authentic acte created by notariary as well Partij Acte and Relaas Acte. In those acte, notariary responsibility exits namely legal responsibility devided into crime responsibility, private, profession and moral. The making of Partij Actes in Article 4 Law No. 30/2004 on notariary which regulate the desires of parties, but in this case, notariary still has responsibility to examineaccording to the parties desire with legal regulation. Acte of Parties (Relaas Acte) regulated in article 46 Law No. 30/2004 on notariary, notariary fully responsible on acte created and the acte can not be sued but the fake of statement in acte.